2022
DOI: 10.4110/in.2022.22.e18
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Mitochondrial ATP Synthesis Induces RIPK3-dependent Necroptosis in Lung Epithelial Cells During Lung Injury by Lung Inflammation

Abstract: Dysfunction of mitochondrial metabolism is implicated in cellular injury and cell death. While mitochondrial dysfunction is associated with lung injury by lung inflammation, the mechanism by which the impairment of mitochondrial ATP synthesis regulates necroptosis during acute lung injury (ALI) by lung inflammation is unclear. Here, we showed that the impairment of mitochondrial ATP synthesis induces receptor interacting serine/threonine kinase 3 (RIPK3)-dependent necroptosis during lung injury by lung inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, the regulatory pathway of necroptosis in the pathophysiological mechanism of ALI has not been elucidated. Researchers specifically focused on the life and death of mitochondria and the role of inflammatory factors represented by tumor necrosis factor in the pathophysiological mechanism of ALI/ARDS [ [50] , [51] , [52] ]. Pyroptosis is a new way of cell death in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…However, the regulatory pathway of necroptosis in the pathophysiological mechanism of ALI has not been elucidated. Researchers specifically focused on the life and death of mitochondria and the role of inflammatory factors represented by tumor necrosis factor in the pathophysiological mechanism of ALI/ARDS [ [50] , [51] , [52] ]. Pyroptosis is a new way of cell death in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that both RIPK3 and MLKL expressions were elevated in LPS-induced lung injury mouse models. 22,23 Geng et al 24 found that LPS could activate RIPK3/MLKL-mediated necroptosis in oral epithelial cells. However, in our study, LPS did not induce necroptosis of nasal polyps, which may be due to the interaction of multiple cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant mitochondrial metabolism mediates cell damage and death 76 . Inhibition of mitochondrial ATP synthesis via oligomycin triggers RIPK3‐based necroptotic signaling in pulmonary epithelial cells in the settings of LPS‐induced ALI 77 . L‐OPA1 is an important mitochondrial inner membrane fusion protein, and the loss can impair mitochondrial functions 78,79 .…”
Section: The Key Molecular Mechanisms Underlying Necroptosis Of Speci...mentioning
confidence: 99%
“…76 Inhibition of mitochondrial ATP synthesis via oligomycin triggers RIPK3-based necroptotic signaling in pulmonary epithelial cells in the settings of LPS-induced ALI. 77 L-OPA1 is an important mitochondrial inner membrane fusion protein, and the loss can impair mitochondrial functions. 78,79 L-OPA1 is downregulated in alveolar epithelial cells upon LPS challenge.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%